Analisis Investasi dan Kelayakan Ekonomi Penambangan Batu Gamping PT Akarna Marindo di Kecamatan Cipatat, Kabupaten Bandung Barat, Provinsi Jawa Barat - Kevin Zen Rizal Pratama; Zaenal; Indra Karna Wijaksana (Bandung Conference Series: Mining Engineering, 2023)
Abstract. PT Akarna Marindo is one of the companies engaged in mining with the commodity of limestone in Cipatat Village, Cipatat District, West Bandung Regency, West Java Province. It is necessary to carry out an analysis of the investment and economic feasibility of the mine to fulfill one of the requirements in extending the ongoing mining business permit. The economic analysis used is based on production costs, investment costs, cash flow and income from the sale of limestone. Considering this, an economic analysis is carried out based on the concept of Discontinued Cash Flow Rate of Return (DCFROR) and sensitivity analysis. The economic criteria used are Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PBP), as well as sensitivity analysis of selling prices and production costs. DCFROR analysis is one of the analytical techniques related to investment, by calculating the value of money against the discount rate using the Weighted Average Cost of Capital (WACC) method which is 8.00%. Then the cash flow calculation is carried out every year to evaluate the cash value based on cash inflows and cash disbursements generated during mining activities. The results of the DCFROR analysis that has been carried out, obtained an NPV value of IDR 5,011,899,460, -, an IRR of 18.60% and a PBP for 3 years and 6 months. It is necessary to evaluate the value of investment uncertainty by determining the level of profit obtained based on changes in various sensitivity parameters. The parameters used in this analysis are selling prices and production costs to the NPV value due to changes in selling prices and production costs. The results of the sensitivity analysis show that selling prices have decreased by more than 8% and production costs have increased by more than 22%. Abstrak. PT Akarna Marindo merupakan salah satu perusahaan yang bergerak dalam bidang pertambangan dengan komoditi batu gamping di Desa Cipatat, Kecamatan Cipatat, Kabupaten Bandung Barat, Provinsi Jawa Barat. Perlu dilakukan analisis investasi dan kelayakan ekonomi tambang untuk memenuhi salah satu syarat dalam memperpanjang izin usaha penambangan yang sedang berlangsung. Analisis ekonomi yang digunakan berdasar pada biaya produksi, biaya investasi, aliran kas dan pendapatan dari penjualan batu gamping. Mempertimbangkan hal tersebut, maka dilakukan analisis ekonomi berdasarkan pada konsep Discontinued Cash Flow Rate of Return (DCFROR) dan analisis sensitivitas. Kriteria ekonomi yang digunakan adalah Net Present Value (NPV), Internal Rate of Return (IRR), Payback Periode (PBP), serta analisis sensitivitas terhadap harga jual dan biaya produksi. Analisis DCFROR menjadi salah satu teknik analisis yang berhubungan dengan investasi, menghitung nilai uang terhadap discount rate menggunakan metode Weighted Average Cost of Capital (WACC) yang didapat sebesar 8,00%. Kemudian perhitungan aliran kas dilakukan setiap tahun untuk mengevaluasi nilai kas berdasar pada pemasukan kas dan pengeluaran kas yang dihasilkan selama kegiatan penambangan. Hasil dari analisis DCFROR yang telah dilakukan, didapat nilai NPV sebesar Rp 5.011.899.460,. IRR sebesar 18,60% dan PBP selama 3 tahun 6 bulan. Perlu dilakukan evaluasi terhadap nilai ketidakpastian investasi dengan menentukan tingkat keuntungan yang didapat berdasarkan perubahan parameter sensitivitas yang bervariasi. Parameter yang digunakan berupa harga jual dan biaya produksi terhadap nilai NPV akibat perubahan harga jual dan biaya produksi. Hasil dari analisis sensitivitas adalah harga jual mengalami penurunan diatas 8% serta biaya produksi mengalami kenaikan diatas 22%.